Association of periodontal infections with atherosclerotic and pulmonary diseases - Scannapieco, F. A.; Genco, R. J. (Journal of periodontal research, 1999)
Chronic infections may influence the severity and/or course of a number of systemic diseases. Periodontal diseases are localized chronic inflammatory conditions of the gingiva and underlying bone and connective tissues induced by bacteria and bacterial products of dental plaque. This paper will discuss the evidence for the role of periodontal disease in the pathogenesis of 2 important systemic diseases, atherosclerosis and pulmonary infections. Both epidemiological and laboratory studies are reviewed to assess the biological basis for the association of periodontal infections and these important diseases. Several potential mechanisms by which periodontal diseases may influence these conditions are also discussed.